The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.14245/ns.1938440.220
|View full text |Cite
|
Sign up to set email alerts
|

Image-Based Markers Predict Dynamic Instability in Lumbar Degenerative Spondylolisthesis

Abstract: Objective: To identify possible radiographic predictors markers of dynamic instability including disc height (DH), disc degeneration, and spondylosis in the setting of degenerative spondylolisthesis (DS). Methods: A retrospective review with prospectively collected data was performed on 125 patients with L4-5 DS who underwent decompression and fusion. Patients were divided into groups with dynamic instability and those without. Radiographs of the lumbar spine in neutral, flexion, and extension were used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
2
7
1
Order By: Relevance
“…Similar to prior studies, 37 we found that maintenance of disk height is associated with instability. We assessed disk height as an index instead of a continuous variable to account for wedge-shaped disks and allowing comparison between patients to be more reliable.…”
Section: Dhisupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to prior studies, 37 we found that maintenance of disk height is associated with instability. We assessed disk height as an index instead of a continuous variable to account for wedge-shaped disks and allowing comparison between patients to be more reliable.…”
Section: Dhisupporting
confidence: 91%
“…Previous studies have investigated reliability of the measurement methods included in our study, and revealing excellent agreement in both intraobserver and interobserver reliability for facet effusion 7,10,35 and FJA, 34 translation 16,42 and DHI. 37 We therefore found a reliability study redundant.…”
Section: Strengths and Limitationsmentioning
confidence: 98%
“…As reported by Kirkaldy-Willis, the accumulation of microscopic degenerative damage caused decreased intervertebral disc height and subluxation of the facet joints, which finally led to increased intervertebral instability [ 27 ]. Compared with the ratios ranging from 31 to 40% reported by previous studies [ 28 30 ], the proportion of unstable spondylolisthesis reached 58.4% in our study (Table 1 ). These discrepancies might be related to age and racial/ethnic composition.…”
Section: Discussioncontrasting
confidence: 79%
“…This defect mostly happens at levels L4-L5 and L5-S1. 3 In low-grade spondylolisthesis, the spino-pelvic parameters change to compensate for the variations of spine mobility. 4 Diminishing of the lumbar lordosis (LL) is followed by a reversed ratio of extensors/ flexors muscle power compared with normal controls.…”
Section: Introductionmentioning
confidence: 99%